If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -9) + -7 = 6(x + -3) Reorder the terms: 6(-9 + 4x) + -7 = 6(x + -3) (-9 * 6 + 4x * 6) + -7 = 6(x + -3) (-54 + 24x) + -7 = 6(x + -3) Reorder the terms: -54 + -7 + 24x = 6(x + -3) Combine like terms: -54 + -7 = -61 -61 + 24x = 6(x + -3) Reorder the terms: -61 + 24x = 6(-3 + x) -61 + 24x = (-3 * 6 + x * 6) -61 + 24x = (-18 + 6x) Solving -61 + 24x = -18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -61 + 24x + -6x = -18 + 6x + -6x Combine like terms: 24x + -6x = 18x -61 + 18x = -18 + 6x + -6x Combine like terms: 6x + -6x = 0 -61 + 18x = -18 + 0 -61 + 18x = -18 Add '61' to each side of the equation. -61 + 61 + 18x = -18 + 61 Combine like terms: -61 + 61 = 0 0 + 18x = -18 + 61 18x = -18 + 61 Combine like terms: -18 + 61 = 43 18x = 43 Divide each side by '18'. x = 2.388888889 Simplifying x = 2.388888889
| x^2+6x+-55=0 | | .5(2x-2)=5x+4 | | f(x)=(x+6)-49 | | 48y^2-13y=0 | | -29=5(2a-1)+3 | | 4(x+2)=8(x-1)-12 | | 2n^2+11n-90=0 | | 7.512=4.2/x | | 9y^2-18=0 | | 4(2+3c)=96 | | -4(1-3b)=21+7b | | 11x-(3x-8)=64 | | 2(4z+4)-9=55 | | 4K+2=5.5 | | -6x=7+5x+5x | | 0x-6y=30 | | h(x)=(x+4)(x-6)(x-8) | | 7z+1/9=8z+2/9 | | 2/3n=46 | | 2x-7x+67=3x+35 | | y/6= | | -3+2(8b-5)=7-31 | | (h+3)(h)-54=0 | | 5x+4/9=6x+7/9 | | -2/5x-8=20+3/4x | | 10=m+8 | | (3x+1)(8x-3)=0 | | -2/5x-8=203/4x | | 4(x+7)=6x+6-2x+22 | | 20-6x=150 | | a+b+2b+3a= | | 4(x+7)=6-2x+22 |